Juvenile recurrent parotitis: clinical, sialographic and ultrasonographic features - MOHAIDEEN SITHEEQUE, YALINI SIVACHANDRAN, VIDYA VARATHAN (IAPD and Blackwell, 2007)
Juvenile recurrent parotitis (JRP) is a rare salivary gland disease of obscure aetiology that affects children. The aim of this study was to investigate the patterns of clinical presentation, and the sialographic and ultrasonographic features of JRP in Sri Lankan children.